LANGUAGE SKILLS INDONESIA AND ARAB IN CHILDREN USING COMPUTER BASED VISUAL BASIC 6.0 - Agus Sulaeman; Aqwam Rosadi Kardian, SKom, MM Aqwam Rosadi Kardian, SKom, MM (Jurnal Sistem Informasi, 2004)
Abstract:Various methods of reading can be taught to children, there was a fast one slow. Afterthe current can be increased understanding. In this reading method, children areexpected to have the mental, memory and intelligence that makes these childrenbecome skilled in speaking. In addition, children are expected to understand what hasbeen read.In scientific writing, the writer wanted to try to create a computer application whichaims to make children prefer to read and speak with interact with computers. Inmaking this application writer use Visual Basic 6.0 programming language.